Utilization of Pineapple Juice Base Growth Medium for Lipid Production by Xanthophyllomyces dendrorhous - Andriani, Ria Dewi; Akeprathumchai, Saengchai; Laoteng, Kobkul; Poomputsa, Kanokwan; Mekvichitsaeng, Phenjun (Jurnal Teknologi Pertanian, 2013)
The main objective of this study lies in utilization of pineapple juice concentrate, an agricultural by-product derived from canned pineapple industry, as a low cost base growth medium to cultivate and simultaneously produce lipid by the red yeast X. dendrorhous. Pineapple juice was characterized and revealed that sucrose, glucose, and fructose were present at the concentration of 23.58, 39.14, and 36.86 g/L, respectively. In addition, acetic acid, citric acid, propionic acid concentrations of 21.70, 2751.30, and 51.00 mM were found to be the main acid in pineapple juice concentrate together with several amino acids; therefore, it possible to employ as base culture medium to cultivate X. dendrorhous. Results on cultivation of X. dendrorhous in the concentration of total sugar 10 g/L pineapple juice without supplemented of nitrogen source was satisfactory in comparison with that of yeast medium. Biomass and lipid content obtained of when cultivated X. dendrorhous in pineapple juice were of 5.14 g/L and 8.90 % in dry cell weight, respectively, while biomass and lipid content when cultivated in yeast medium were 4.88 g/L and 4.10 % in dry cell weight, respectively. Since yeast medium was rather expensive, moreover, cultivation of X. dendrorhous in pineapple juice concentrate, a low cost substrate, was fairly reasonable. Therefore, pineapple juice could be an excellent substrate for cultivating X. dendrorhous when appropriately optimized.Keywords: biomass, lipid, X. dendrorhous, pineapple juice